EXPANSION OF INTERACTION BETWEEN LAW ENFORCEMENT INTELLIGENCE-GATHERING AND CRIMINALLY REMEDIAL ACTIVITIES AS A FACTOR IN THE DEVELOPMENT OF EVIDENCE SYSTEM OBTAINED WHEN INSTITUTING CRIMINAL PROCEEDINGS - Inna V. Makeeva, Marianna O. Rumyantseva, Rayganat I. Naibkhanova, ?lena ?. Kolomoets, Nikita S. Grudinin (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The relevance of the studied problem is due to the issues that arise when expanding the interaction of law enforcement intelligence-gathering and criminally remedial activities; the current situation in the Russian Federation, as well as difficulties in the development of evidence system obtained when instituting criminal proceedings. In this regard, this article is aimed at a comprehensive analysis of the issues of determining the evidence reliability. The leading approach to the study of this problem is the analysis of the perception of the criminal procedure law of the provisions on the presentation of the results of law enforcement intelligence-gathering activities. The article summarizes the problematic issues related to the lack of criminal procedure regulation of the use of law enforcement intelligence-gathering tools in order to verify existing evidence, as well as the doctrinal approach to the subject under consideration. The materials of the article can be useful for law enforcement officers, as well as for students, undergraduates and postgraduates studying in the field of "World of Law".